2011
DOI: 10.1053/j.gastro.2010.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Composition of the Human Gastrointestinal Microbiome and Development of Fatty Liver With Choline Deficiency

Abstract: BACKGROUND & AIMS-Non-alcoholic fatty liver disease affects up to 30% of the U.S. population, but the mechanisms underlying this condition are incompletely understood. We investigated how diet standardization and choline deficiency influence the composition of the microbial community in the human gastrointestinal (GI) tract and the development of fatty liver under conditions of choline deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
406
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(430 citation statements)
references
References 52 publications
16
406
0
8
Order By: Relevance
“…Choline is also important for lipid metabolism and synthesis of very-low-density lipoprotein in the liver, and insufficient levels in the diet are associated with altered gut microbial ecology and liver steatosis in mice 56 and humans 57 . In particular, low quantities of Gamma-proteobacteria and high levels of Erysipelotrichi in human faecal microbiota are associated with hepatic steatosis 57 .…”
Section: Microbial Metabolism Of Cholinementioning
confidence: 99%
“…Choline is also important for lipid metabolism and synthesis of very-low-density lipoprotein in the liver, and insufficient levels in the diet are associated with altered gut microbial ecology and liver steatosis in mice 56 and humans 57 . In particular, low quantities of Gamma-proteobacteria and high levels of Erysipelotrichi in human faecal microbiota are associated with hepatic steatosis 57 .…”
Section: Microbial Metabolism Of Cholinementioning
confidence: 99%
“…Choline metabolism is mainly disrupted by 3 main bacterial phyla in the gut microbiota: Proteobacteria, Firmicutes, and Actinobacteria (130). Spencer et al (131), in a longitudinal experimental study in healthy women who consumed a rigorously controlled diet, showed that choline deficiency led to hepatic lipid accumulation. In addition, decreased amounts of Gammaproteobacteria and increased Erysipelotrichi were directly associated with elevated accumulation of hepatic fat.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular -diseased mice and microbial metabolism (WANG et al, 2011); 8. Nonalcoholic fatty liver disease-effect of choline depletion in human (SPENCER et al, 2011). 9.…”
Section: Gut Microbioma and Healthmentioning
confidence: 99%
“…Several diseases, however, are so important that they are worth including in this review, e.g., nonalcoholic fatty liver disease, which affects 30% of the USA population (SPENCER et al, 2011). The nonalcoholic fatty liver represents an association between composition of human gastrointestinal microbiome and the development of fatty liver, with choline deficiency as an additional risk for developing atherosclerosis and CVD.…”
Section: Visceral Obesitymentioning
confidence: 99%